Use of recycled concrete fines in cement and as aggregate - Simone Stuerwald; Ronny Meglin; Susanne Kytzia; Sabrina Gilg (Acta Polytechnica CTU Proceedings, 2022)
The research project focused on investigating and optimizing the processing and use of recycled crushed sand 0/4 from concrete demolition waste, as an alternative raw material in the cement and concrete industry. Crushed sand is produced during the processing of concrete demolition waste. The goal was to identify the optimum way of using the processed material along the entire process chain so that greenhouse gas emissions, waste volumes are reduced, and natural resources are conserved. Different samples of laboratory and real crushed concrete fines were collected and examined in relation to various possible applications in accordance with the applicable standards. Results highlight, that crushed concrete fines can be used in various applications in the concrete value-chain. However, for an optimal usage, additional processing is needed.